Comparison of postoperative analgesia and sedation responses of intravenous dexmedetomidine and esmolol during laparoscopic cholecystectomy - Zuberi, Azka; Masoodi, Tahir Ahamad; Rastogi, Bhawana; Gupta, Rajni; Malik, Anita; Farooqui, Raza (International Journal of Research in Medical Sciences, 2019)
Background: Although, the concept of laparoscopic surgeries has revolutionised the surgical practice and has markedly reduced the incidence of complications especially postoperative pain. However, the menace of postoperative pain still remains challenge, especially in first 24 hours. The present study was conducted to comparatively analyse the postoperative pain and sedation using intravenous dexmedetomidine and intravenous esmolol during laparoscopic cholecystectomy. Methods: Study was conducted on 90 adult patients aged 18-60 years of ASA grade I or II of both genders, scheduled for laparoscopic cholecystectomy under general anaesthesia. Patients were randomized into three groups of 30 patients each. Patients of group A received esmolol infusion (loading: 1 mg/kg and maintenance: 5-15 µg/kg/min), patients of group B received dexmedetomidine infusion (loading: 0.7 µg/kg and maintenance: 0.4 µg/kg/hour) and group C (control group) received normal saline infusion. During the post-operative period of 24 hours, patient were monitored for sedation using Ramsay sedation score like pain, using visual analogue score (VAS), incidence of post-operative nausea and vomiting and use of any drug for pain, vomiting and any other side effect. Results: Frequency of pain was highest in group C at all post periods, followed by group A and was least in group B. The mean sedation score of group B was comparatively higher as compared to both group C and group A. Conclusions: The inference authors drew was that dexmedetomidine is better analgesic with aurousable sedation.